Comparison of time consumption and success rate between CT angiography- and CT perfusion- based imaging assessment strategy for the patients with acute ischemic stroke - Yue Chu; Gao Ma; Xiao-Quan Xu; Shan-Shan Lu; Hai-Bin Shi; Sheng Liu; Qiang-Hui Liu; Fei-Yun Wu (BMC Medical Imaging, 2022)
Abstract Background Our study aimed to compare the time consumption and success rate between CTA- and CTP- based assessment strategy, and to clarify the risk factors associated with the CTP scan failure. Methods Clinical and radiological data of 437 consecutive AIS patients who underwent multiphase CTA or CTP for pre-treatment evaluation were retrospectively enrolled (CTA group, n = 302; CTP group, n = 135). Time consumption and success rate of CTA- and CTP- based assessment strategy were compared using Mann–Whitney U test and Chi-Squared Test. Univariate analysis and receiver operating curve analysis were used to clarify the risk factors, and their performance in predicting the CTP scan failure. Results Time consumption of CTP scan and reconstruction was significantly longer than that of CTA [775 s vs 263.5 s, P < 0.001]. CTP scan showed significantly higher failure rate than CTA (11% vs 1%, P < 0.001). Severe motion was the most common cause of CTP failure (n = 12, 80%). Baseline National Institute of Health Stroke Scale (NIHSS) score in CTP failure group was significantly higher than that in CTP success group [17 vs 13, P = 0.007]. Baseline NIHSS score of 11 was the optimal threshold value to predict CTP failure with an area under the curve of 0.715, a sensitivity of 86.7%, and a specificity of 45.0%. Conclusions CTP- based strategy showed longer time consumption and higher failure rate than CTA- based strategy. High baseline NIHSS score was significantly associated with CTP scan failure in AIS patients.